Impact of Diesel Exhaust Particles on Th2 Response in the Lung in Asthmatic Mice - Inoue, Ken-ichiro (the Society for Free Radical Research Japan, 2008)
Although it has been accepted that pulmonary exposure to diesel exhaust particles (DEP), representative constituents in particulate matter of mass median aerodynamic diameter < or 2.5 µm (PM(2.5)), exacerbates murine allergic asthma, the in vivo effects of DEP on their cellular events in the context of allergen-specific Th response have never been examined. The aim of this study is to elucidate whether in vivo repetitive exposure to DEP combined with allergen (ovalbumin) facilitate allergen-specific Th response in the lung using a simple ex vivo assay system. As a result, repetitive pulmonary exposure to DEP in vivo, if combined with allergen, amplifies ex vivo allergen-specific Th2 response in the lung compared to that to allergen alone, characterized by high levels of interleukin (IL)-4 and IL-5. The result suggests that in asthmatic subjects, DEP promote Th2-prone milieu in the lung, which additively/synergistically augment asthma pathophysiology in vivo.